IMPACT OF WORKLOAD, WORK ENVIRONMENT AND STRESS LEVEL ON EMPLOYEE MENTAL HEALTH AT XYZ OFFICE - Dewi Puspaningtyas Faeni; Sulung Anom Prayogo (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
The study aimed to determine the impact of work stress, work area and stress level on the mental health of employees of Department XYZ. Data analysis of the interactive model according to Miles and Huberman was used in this research. In this study, data collection was conducted to analyze and interview observations were recorded during data collection time. The result of the study is that workload, work environment and stress level have a significant influence on the mental health of employees in the XYZ Department. Work stress can affect the mental health of employees, especially when working hours and hours increase. The work environment has an influence on the mental health of employees, a good and positive environment can make the workplace feel like home, a bad work environment can harm the mental health of employees. Work stress is a major problem for companies in terms of good and bad employee mental health. One way to prevent and anticipate job stress in management is to identify stressful jobs and establish and implement them properly.